Running towards health: the association of running volume with running-related injuries - Nakaoka, Gustavo Bezerra (2020)
Background: Running-related injuries (RRI) may lead to drop out from running practice and reduce the likelihood of keeping up a physically active lifestyle. Training workload could be either a risk or a protective factor for sports-related injuries. The acute:chronic workload ratio (ACWR) is a method that considers the current (i.e., acute workload) sport workload performed by an individual in relation to the workload this individual is prepared for (i.e., chronic workload). Purpose: To investigate the longitudinal association between the ACWR and RRIs. Methods: This is a secondary analysis using a database composed of data from three studies conducted with the same surveillance system in the Netherlands. Longitudinal data were collected biweekly. Bayesian logistic mixed models were used to analyse the data. A time-lag technique was applied to the RRI incidence data to ensure that the running workload was collected before the reporting of the RRIs. The uncoupled ACWR was calculated as the most recent workload divided by the average of the previous three biweekly periods. The model was adjusted for age, sex, body mass index, running experience and previous RRIs. Repeated measurements and cohort samples based on the studies included in this analysis were included as random effects. Results were presented as odds ratio (OR) and the 95% credible interval (95% CrI). Results: The sample was composed of 435 Dutch runners (276 males). Although significant, the relation between RRIs and the ACWR was found to vary from small to moderate (1% to 10%) with a tendency pointing out higher ACWR related to lower RRIs risk. For external workloads calculated using exposition in hours, runners whose ACWR were under 0.65 had a 9% probability of sustaining an RRI (i.e., 0.09 [95% CrI 0.07 to 0.12]). Conclusions: In runners, the ACWR showed an association with RRIs approximately linear and inversely proportional. Being a useful tool indicating injured runners reducing their training workload.